Key Technology of SSL Encrypted Application Identification Under Imbalance of Application Class - Xuejiao Chen; Pan Wang; Shidong3 Liu (Dianxin kexue)
Through a in-depth study about the reason of network class imbalance, a method called SMOTE was chosen over the data set sampling preprocess, making full use of the advantages which is high accuracy of traffic model feature matching identification and sorting out the encrypted SSL flow, and then using the clustering method and the SVM based on mutual information classification method to further identify SSL encryption specific application, like HTTPS/POPS etc. The hybrid method effectively combines the advantages of static feature matching and machine learning methods,to achieve the balance of classification method on accuracy and speed.